Pengaruh Mitos dalam Melestarikan Objek Wisata Air Terjun Nglirip: Kajian Budaya dan Pariwisata - Munjiyat, Sella Ainun; hasaniyah, nur (Maliki Interdisciplinary Journal, 2025)
This article examines the stories, myths, and appeal of Nglirip Waterfall in Tuban as a tourist attraction that combines natural beauty with local legends. The study focuses on the role of myths in enhancing the destination’s popularity and its impact on the cultural identity of the local community. A qualitative approach was used to explore the perceptions of the community and visitors through in-depth interviews, field observations, and documentation. The results show that the “Wounded Princess” legend provides a mystical charm that enriches the tourist experience and strengthens the local cultural image. This narrative not only attracts tourists but also serves as a form of cultural preservation passed down through generations. This research offers insights into the importance of integrating folklore elements in tourism development and cultural preservation, as well as providing a new perspective on how local myths can contribute to sustainable tourist appeal.